Caracterización de la economía circular en el sector de la construcción mediante su análisis e implementación en la ciudad de Bogotá - Colombia (2021)
In this monograph the concepts of circular economy and sustainable constructions are analyzed, in which a characterization of the current situation of the construction sector in the city of Bogotá is made, likewise, the basic principles of the circular economy were analyzed by making a identification of construction companies that are involved in the issue, giving guidelines for any company in the sector to change its economic model from linear to circular, making the sector more environmentally competitive.